2016
DOI: 10.1017/s0025315416000837
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variability of the potentially toxic Pseudo-nitzschia spp. in a eutrophic estuary (Sea of Marmara)

Abstract: Spatial and temporal variability and bloom formation of the potentially toxic diatom Pseudo-nitzschia spp. was investigated weekly to monthly from in a eutrophic estuary, the Golden Horn. Pseudo-nitzschia spp. were detected in 195 of 512 samples (38%) collected throughout the year. Two species, P. calliantha and P. pungens, were identified based on the SEM examination. Blooms of Pseudo-nitzschia occurred in the lower and middle estuary in January and May. The bloom in January mainly comprised P. calliantha. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…During the sampling period, Pseudo-nitzschia species were found at a wider range of salinity (13.05 to 20.18) than in the previous study (Tas &Lundholm, 2015), but they reached highest cell density at 18.4 in late May 2012 along similar lines with the current study. The high Pseudo-nitzschia abundances with low temperatures and high salinity is similar to the pattern for P.calliantha in the Adriatic Sea (Caroppo, Congresti, Bracchini, & Albertano, 2005) and Pseudo-nitzschia spp.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…During the sampling period, Pseudo-nitzschia species were found at a wider range of salinity (13.05 to 20.18) than in the previous study (Tas &Lundholm, 2015), but they reached highest cell density at 18.4 in late May 2012 along similar lines with the current study. The high Pseudo-nitzschia abundances with low temperatures and high salinity is similar to the pattern for P.calliantha in the Adriatic Sea (Caroppo, Congresti, Bracchini, & Albertano, 2005) and Pseudo-nitzschia spp.…”
Section: Discussionsupporting
confidence: 88%
“…P. delicatissima and P. pungens were present in almost every year between June 1998 and May 2002 with the highest abundance (1.6×10 6 cells L -1 ) in May and June (Tas et al, 2009). In another study carried out at the GHE, two blooms of Pseudonitzschia were reported in Jan. and May 2010 (Tas & Lundholm, 2015); however no study was performed on domoic acid occurence in the area.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Understanding the relationships between the abundance of these diatoms, DA, and the characteristics of the environment will provide valuable information on the variable(s) that might determine their growth, distribution, and DA production. Several authors [18][19][20][21][22][23][24] have related these…”
Section: Introductionmentioning
confidence: 99%